A systematic literature review on the importance of teacher recruitment and retention in global educational reform - Shaoan, Md Mirajur Rhaman; Namanyane, Tebatso; Feng, Meiqi; Arif, Muhammad (Frontiers in Education, 2025)
This study conducts various economic approaches implemented worldwide to augment teachers’ recruitment and retention. It commences by situating the criticality of teacher recruitment and retention within the broader ambit of educational expansion and reform worldwide. Each nation prioritizes recruiting and retaining high-caliber educators, acknowledging the critical role that remuneration and additional professional opportunities play in attracting and sustaining individuals within the teaching profession. This systematic literature review analyzes the Economic approaches to teacher recruitment and retention. Using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysis Protocols Statement), this literature review is those articles successfully published between 2017 and 2023. The study uses two well-known internet sources: Web of Science and Scopus. There are 215 publications, including 15 papers with the most citations for this thorough literature study. This study emphasizes the importance of economic incentives, such as salary and professional development opportunities, in attracting and retaining skilled teachers in educational institutions. This study finds that policymakers and educational administrators worldwide have pertinent insights and data poised to aid in formulating more efficacious economic strategies for recruiting and retaining teachers. The recommendations are based on a nuanced understanding of the interplay between financial factors and educational efficacy, seeking to inform future policy directions and academic discourse in this field.